The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12885-019-5810-2
|View full text |Cite
|
Sign up to set email alerts
|

TSPAN9 and EMILIN1 synergistically inhibit the migration and invasion of gastric cancer cells by increasing TSPAN9 expression

Abstract: Background Globally, the incidence and mortality rates of gastric cancer are high, and its poor prognosis is closely related to tumor recurrence and metastasis. Therefore, the molecular mechanisms associated with the migration and invasion of gastric cancer cells are important for gastric cancer treatment. Previously, TSPAN9 has been reported to inhibit gastric cancer cell migration; however, the underlying molecular mechanism remains unclear. Methods Human gastric aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Second, TSPAN9 (tetraspanin-9) belongs to a protein superfamily that is involved in cell development, differentiation, mobility, as well as in tumour proliferation and invasion. In particular, the role of TSPAN9 in cancer has not been thoroughly explored: a lower level of expression in gastric cancer than in non-neoplastic gastric tissue [28], and some anti-tumour effects in vitro gastric models [29,30], are the only findings reported so far. In contrast, here, we described a higher level of expression of TSPAN9 in TNBC than in non-neoplastic counterparts, suggesting that TSPAN9 might have a tumour-dependent molecular status and role.…”
Section: Discussionmentioning
confidence: 99%
“…Second, TSPAN9 (tetraspanin-9) belongs to a protein superfamily that is involved in cell development, differentiation, mobility, as well as in tumour proliferation and invasion. In particular, the role of TSPAN9 in cancer has not been thoroughly explored: a lower level of expression in gastric cancer than in non-neoplastic gastric tissue [28], and some anti-tumour effects in vitro gastric models [29,30], are the only findings reported so far. In contrast, here, we described a higher level of expression of TSPAN9 in TNBC than in non-neoplastic counterparts, suggesting that TSPAN9 might have a tumour-dependent molecular status and role.…”
Section: Discussionmentioning
confidence: 99%
“…Modica et al (2017) founded that EMILIN1 can silences the RAS-ERK pathway via alpha4beta1 integrin, decreasing tumor cell growth. Qi et al (2019) confirmed that EMILIN1 regulates the expression of TSPAN9, creating an anti-tumor effect in gastric cancer. However, there is no current research on the significance of EMILIN1 in patients with LGG.…”
Section: Discussionmentioning
confidence: 57%
“…In subsequent studies, we mainly studied the role of Tspan7 in liver cancer cells. Since the fourtransmembrane protein family also directly or indirectly participates in the process of cell proliferation, invasion and metastasis, we hope to understand what role Tspan7 plays in liver cancer cells [9,[28][29][30] . The results showed that the high expression of Tspan7 not only inhibited the proliferation of HCC-LM3 cells but also inhibited the invasion and metastasis of liver cancer cells.…”
Section: Discussionmentioning
confidence: 99%